Design Of Diagnosis Expert System Of Car Damage On Auto 2000 Kenjeran Surabaya Using A Rule Based System Method - Hikam, Dicky Sirojul; Jusak, Jusak; Lemantara, Julianto (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2021)
Auto 2000 is a network of sales, repair, parts providers of Toyota, and maintenance that management is fully handled by a company. Astra Internasional Tbk. Auto 2000 is currently the largest automotive company in Indonesia which controls approximately 42% of Toyota's total sales. Auto 2000 there is a workshop that will serve or meet customer complaints contained in cars under the Toyota brand. Currently what happens in Auto 2000 Kenjeran, especially in the workshop service advisor (SA) is still looking for solutions or actions in case of problems with the car. At the time of checking by frequent customer waiting times become long, it creates a queue of cars to check for damage to the car. The misdiagnosis of damage by SA will be returned by the SA to recheck the damage done to the customer's car. By using the rule-based system method this method will work well when the problem starts from collecting / uniting information and then looking for what conclusions can be drawn from the information is able to analyze the kind of damage that occurs in the car engine. Questionnaire results from each position as follows, the head of the workshop gets a result of 100% with a percentage of the value is very appropriate, PTM gets a result of 100% with a percentage of very suitable value, FO gets a result of 96.66% with a percentage of very suitable value, SA gets a result of 99.16% with a percentage of very suitable value. The result of the alignment of positions is 99.10% which in the percentage of the value of the figure is included in the category is very appropriate.